Effects of Na Excess on the Preparation and Characterization of (K0.5Na0.5)NbO3 Ceramics. Issue 1 (26th January 2016) - Tian, Aifen; Li, Ce; Fan, Jinyu; Li, Lei; Xu, Zhipeng; Du, Huiling
Abstract : Lead free ceramics (K0.5 Na0.5+x )NbO3 (0 ≤ x ≤ 0.3, KNN-x) were prepared by a novel method mixing perovskite structure of NaNbO3 and KNbO3 powders. Effects of Na excess and sintering temperatures on phase structure, microstructure and electrical properties of KNN ceramics were investigated. Result showed that the single phase perovskite structure was obtained in the KNN-0.1 ceramic sintered at 1070°C, which also showed optimized ferroelectric property with Pr = 7.16 μC/cm 2 and Ec = 7.95 kV/cm. The KNN-x ceramic with x = 0.2 showed optimized piezoelectric property with d33 = 116 pC/N because of the homogeneous dense microstructure.